2018
DOI: 10.1111/1462-2920.14454
|View full text |Cite
|
Sign up to set email alerts
|

Formate cross‐feeding and cooperative metabolic interactions revealed by transcriptomics in co‐cultures of acetogenic and amylolytic human colonic bacteria

Abstract: Summary Interspecies cross‐feeding is a fundamental factor in anaerobic microbial communities. In the human colon, formate is produced by many bacterial species but is normally detected only at low concentrations. Ruminococcus bromii produces formate, ethanol and acetate in approximately equal molar proportions in pure culture on RUM‐RS medium with 0.2% Novelose resistant starch (RS3) as energy source. Batch co‐culturing on starch with the acetogen Blautia hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Therefore, acetogens are important microorganisms for the circular bio-economy and for mitigating climate change ( Oren, 2012 ; Liew et al, 2016 ; Müller, 2019 ; Wiechmann and Müller, 2019 ). Acetogens are also abundantly present in the human gut, but their role in human gut physiology and the gut-brain relationship require further investigation (e.g., Gibson et al, 1990 ; Leclerc et al, 1997 ; Ohashi et al, 2007 ; Rey et al, 2010 ; Laverde Gomez et al, 2019 ). Moreover, some acetogens have been found to associate with plants in aquatic habitats and can fix atmospheric nitrogen ( Küsel et al, 1999 ; Pester and Brune, 2006 ; Ohkuma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, acetogens are important microorganisms for the circular bio-economy and for mitigating climate change ( Oren, 2012 ; Liew et al, 2016 ; Müller, 2019 ; Wiechmann and Müller, 2019 ). Acetogens are also abundantly present in the human gut, but their role in human gut physiology and the gut-brain relationship require further investigation (e.g., Gibson et al, 1990 ; Leclerc et al, 1997 ; Ohashi et al, 2007 ; Rey et al, 2010 ; Laverde Gomez et al, 2019 ). Moreover, some acetogens have been found to associate with plants in aquatic habitats and can fix atmospheric nitrogen ( Küsel et al, 1999 ; Pester and Brune, 2006 ; Ohkuma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that by using 0.2% resistant starch as an energy source, R. bromii produces formic acid, ethanol, and acetic acid in approximately equal molar ratios on RUM-RS medium. 9 However, batch co-culture with acetogenic bacteria B. hydrogenotrophica on starch resulted in the disappearance of formic acid with an increase in acetic acid levels. RNA sequencing was used to further study the interspecific interactions to detect gene expression in continuous co-cultures of R. bromii and B. hydrogenotrophica.…”
Section: Cross-feeding Of Blautia With Other Microorganismsmentioning
confidence: 99%
“…Crossfeeding between formic acid-producing species and acetic acid-producing species may play an important role in the formation of SCFAs in the colon and contribute to the massive production of acetic acid. 9 As a key hydrogen-consuming anaerobic microorganism, B. hydrogenotrophica has been reported to mediate regulation related to the coexistence of anaerobic respiratory pathways. B. hydrogenotrophica consumes H 2 and CO 2 via the Wood-Ljungdahl pathway to produce acetic acid -a pathway significantly activated when coexisting with Bifidobacterium bifidum.…”
Section: Cross-feeding Of Blautia With Other Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could increase our understanding of gut ecology and promote the design of a synthetic microbial community representative of balanced human gut microbiota by mapping the keystone species into a stable microbiota and comparing it with diseased microbiota. Experiments involving co-cultures of core gut microbes have shown fascinating cross-feeding pathways, which involve the use of short chain fatty acids (SCFAs) [29] and have identified properties associated with major metabolic pathways for amino acid and vitamin metabolism, in combination with molecular analysis techniques [30] , [31] . There are several routes for obtaining reliable core gut microbiota.…”
Section: Systemic Features Of Gut Ecosystemsmentioning
confidence: 99%